The art of leadership through public relations : the future of effective communication - Schober, Patrik (Emerald Publishing Limited, 2023)
The pandemic, the war in Ukraine and the increasing pace and impact of climate change have brought significant new challenges to leaders of nations, organizations, and professions. These events have changed the way we work, trade and live our lives. They have also changed the expectations on how our leaders must communicate. Stakeholders now expect leaders to have a clear and transparent position on all the key areas that matter most to them. The Art of Leadership through Public Relations: The Future of Effective Communication is designed to address those changed expectations by asking the questions that communications professionals and industry leaders will need to be able to answer in the next 20 years. Public Relations expert Patrik Schober has assembled a cadre of icons of the PR industry who act as part expert and part futurologist, to provide expert advice and enable leaders to be prepared to meet their most important communications and business challenges. The Foreword of the book is written by Francis Ingham, Director General of the PRCA, and Chief Executive of the International Communications Consultancy Organisation.
Keywords: Public relations.; Leadership.; Communication.; Business & Economics, Public Relations.; elektronické knihy; electronic books